Pengaturan Pencurian Barang Penumpang Pesawat dalam UU Penerbangan dan Konvensi Chicago - Almansyah Harahap; Berdi adityas Wiryawan Wahyono; Mochamad Ardhy Sahal Machfudz; Dzakwan Zaidan (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
This article examines the legal regulation of theft of passengers’ belongings on board an aircraft under Indonesian Aviation Law and the 1944 Chicago Convention, using the 2025 Scoot Singapore–Jakarta case involving two Chinese nationals as the focal case. The study addresses the gap between the need to protect passengers’ property in the cabin and the limited specificity of aviation law in regulating theft committed by one passenger against another during an international flight. The research aims to analyze the scope of Law No. 1 of 2009, to assess the relevance of the Chicago Convention 1944, and to evaluate their application to the Scoot case. This study employs normative legal research with statute, case, and conceptual approaches. The materials consist of primary legal sources, international aviation instruments, official documents, and relevant scholarly literature. The findings show that Law No. 1 of 2009 regulates order, safety, and security on board, yet does not formulate theft of passengers’ property as a specific aviation offence. The Chicago Convention 1944 functions as a general framework on sovereignty, aircraft nationality, and the applicability of national law, while the criminal handling of on-board theft is more closely connected with the regime governing offences committed on board aircraft. The study identifies a need for clearer national rules on cabin theft, initial handling procedures, and cross-border jurisdictional coordination.